PERJANJIAN PERKAWINAN ADAT DI MASYARAKAT DAYAK NGADJU KOTA PALANGKARAYA KALIMANTAN TENGAH - , Kintasari, Agus Sudaryanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research was to identify necessity of prenuptial agreement in Dayak Ngadju adat marriage in Palangkaraya, Central Kalimantan and to study legal sanction when one of partij in the marriage violates the agreement content. This research was juridical sociological research that saw law as social symptom and regulation. Main data was primary data obtained directly from research subject. To complete primary data, literary research was done. Data were collected using purposive sampling method, in which sample was determined by taking subject not based on strata, random, or location but based on certain objectives of this research. Subject was 10 (ten) respondents consisting of adat prenuptial agreemement subject. In addition, interview was done with sample persons consist of Damang Kepala Adat, Dayak adat figure and adat prenuptial agreement witnesses. Obtain data were analyzed using qualitative and directed to result in conclusion with inductive logic. The results indicated necessity of adat prenuptial agreement in Dayak Ngadju society due to mores which carried from generation to generation